Evaluation of artifacts of cochlear implant electrodes in cone beam computed tomography - Bevis, Nicholas (Eur Arch Otorhinolaryngol, 2020)
PURPOSE: Cone Beam Computed Tomography (CBCT) offers a valid alternative to conventional Computed Tomography (CT). A possible radiation dose reduction with the use of CBCT in postoperative imaging of CIs is of great importance. Whether the visualization of Cochlear Implant (CI) electrodes in CBCT correlates with the radiation dose applied was investigated in this study. METHODS: We compared the visualization quality of Contour Advance CIs to Straight CIs from Cochlear using CBCT with varying tube parameters on whole-head specimen. RESULTS: The internal diameter of the cochlea decreases from base to apex, resulting in a significantly different intracochlear positioning of the two tested CI models. While electrodes of the Contour Advance series are located close to the modiolus, thus closer to the spiral ganglion neurons, those of the Straight series are located further away. The artifact portion of the electrode amounts to 50–70% of the radiological diameter of the electrode. An increase in artifact portion from the base (electrode #1 approx. 50%) to the apex (electrode #20 approx. 70%) of the cochlea was observed. The visualization of electrodes in the medial and apical part of the cochlea is limited due to artifact overlapping. There was no correlation between the artifact size and the applied radiation dose. CONCLUSION: The results indicate that a reduction of the radiation dose by up to 45% of the currently applied radiation dose of standard protocols would be possible. Investigations of the effects on subjective image quality still need to be performed.